2009
DOI: 10.1002/smll.200801907
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Encapsulation of Hydrophilic and Hydrophobic Drugs in Poly(L‐lactic acid) Nanoparticles

Abstract: An electrospray method is developed for preparation of beclomethasone-dipropionate- and salbutamol-sulfate-loaded biodegradable poly(L-lactic acid) nanoparticles. Different set-up parameters for electrospraying are examined on particle size, and preparation conditions are optimized for producing spherical-drug-loaded nanoscale particles by controllable processing parameters. Polylactide (PLA)-drug nanoparticles with average diameters of around 200 nm are achieved in a stable cone-jet mode with a flow rate of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 54 publications
1
83
0
Order By: Relevance
“…Secondly, the size distributions of particles fabricated by emulsion-based techniques tend to be inhomogeneous and broad, contributing to their lack of reproducibility, which in turn hinders their clinical use. Size distribution is a crucial parameter and it was shown that monodisperse size would enable a better control of release profiles and bioavailability of the loaded drug in the body [12,13]. Particle morphology is also important since it affects the internalization by non-phagocytic cells and the degradation of the polymer matrix which, in turn, determines the release kinetics of the loaded component.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the size distributions of particles fabricated by emulsion-based techniques tend to be inhomogeneous and broad, contributing to their lack of reproducibility, which in turn hinders their clinical use. Size distribution is a crucial parameter and it was shown that monodisperse size would enable a better control of release profiles and bioavailability of the loaded drug in the body [12,13]. Particle morphology is also important since it affects the internalization by non-phagocytic cells and the degradation of the polymer matrix which, in turn, determines the release kinetics of the loaded component.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of drug loading, the bioactive molecule is mixed to the polymer solution before electrospraying and can further be emulsified [21]. Some studies which have been undertaken include encapsulation of hydrophilic and hydrophobic model drugs [12], model proteins [21][22][23][24][25], antibiotics [14,26] and anti-cancer drugs [13] in polylactide (PLA) [12,21], poly(lactic-co-glycolic acid) (PLGA) [24,26], polycaprolactone (PCL) [13,24] and chitosan [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Poly(lactide-co-glycolide) (PLGA), polyhydroxybutyrate (PHB), poly(lactic acid) (PLA), and polycaprolactone (PCL) are examples of polymers that have been electrosprayed into micro-/nanoparticles for drug delivery applications. [20][21][22][23] While these polymers are biocompatible and biodegradable, their hydrophobicity can lead to the formation of unstable suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, high drug encapsulation efficiencies of around 90 per cent have been reported using electrospraying [29,30]. Several research groups have studied the use of electrospraying to prepare polymeric particles for drug-delivery purposes (including [31][32][33]). Drug-loaded microparticles have been produced in sizes ranging between 250 nm and 100 mm depending on the materials used and the processing parameters applied but are most often observed between 1 and 10 mm in diameter [34].…”
mentioning
confidence: 99%